SYNTHESIS OF NEW DERIVATIVES OF 2,5-DIHYDRO-2-OXOFURANS (Proceedings of the YSU B: Chemical and Biological Sciences, 2013)
New derivatives of 2,5-dihydro-2-oxofurans were synthesized by the interaction of 3-acetyl-4,5,5-trimethyl-2,5-dihydro-2-oxofuran with N-nucleophiles containing aromatic and heterocyclic substituents.
Keywords: 3-acetyl-4,5,5-trimethylfuran-2,5-dihydro-2-oxofuran; $N$-nucleophile; antibacterial activity